Plantas de cobertura para o noroeste do estado de São Paulo - Borges, Wander Luis Barbosa; Freitas, Rogério Soares De; Mateus, Gustavo Pavan; Sá, Marco Eustáquio De; Alves, Marlene Cristina (Universidade Federal de Santa Maria, 2014)
This study was conducted to evaluate the productivity of biomass of five cover crops used for the production of grain, seeds and fodder in different sowing density per hectare, and of spontaneous vegetation for the northwest region of São Paulo State, Brazil. The experiments were installed in Votuporanga, SP, Brazil and Selvíria, MS, Brazil in March 2008, after conventional tillage. The experimental design was a randomized complete block with four replications, using the following cover crops at different sowing density: Sorghum bicolor: 6, 7 and 8kg ha-1, Pennisetum americanum, 10, 15 and 20kg ha-1, Sorghum sudanense, 12, 15 and 18kg ha-1, hybrid of Sorghum bicolor with Sorghum sudanense: 8, 9 and 10kg ha-1, Urochloa ruziziensis: 8, 12 and 16kg ha-1. It was used a control treatment with spontaneous vegetation. The biomass of different toppings in harvesting/cutting of covers was evaluated, in the pre-sowing and flowering of soybean and corn. The use of cover crops proved more beneficial than leaving areas fallow. It was concluded that different cover crops evaluated showed to be good options as cover crops for the northwest region of São Paulo State and the different sowing density from each plant cover did not influence biomass productivity of the same plant coverage

O trabalho foi realizado com o objetivo de avaliar a produtividade de fitomassa de cinco plantas de cobertura utilizadas para produção de grãos, sementes e forragem, em diferentes densidades de semeadura, e da vegetação espontânea, na Região Noroeste do Estado de São Paulo. Os experimentos foram instalados em Votuporanga, SP e Selvíria, MS, em março de 2008, após o preparo convencional do solo. O delineamento experimental utilizado foi o de blocos casualizados com quatro repetições, utilizando as seguintes plantas de cobertura em diferentes densidades de semeadura que constituíram os tratamentos: Sorghum bicolor: 6, 7 e 8kg ha-1, Pennisetum americanum: 10, 15 e 20kg ha-1, Sorghum sudanense: 12, 15 e 18kg ha-1, híbrido de Sorghum bicolor com Sorghum sudanense: 8, 9 e 10kg ha-1, Urochloa ruziziensis: 8, 12 e 16kg ha-1. Também se utilizou um tratamento controle com vegetação espontânea. Avaliou-se a fitomassa das diferentes coberturas no momento da colheita/corte das coberturas, na pré-semeadura e no florescimento das culturas da soja e do milho. A utilização de plantas de cobertura mostrou-se mais benéfica que se deixar as áreas em pousio. Concluiu-se que as plantas de cobertura avaliadas mostraram-se como boas opções de plantas de cobertura para a região Noroeste do Estado de São Paulo. Além Disso, as diferentes densidades de semeadura de cada planta de cobertura não influenciaram na produtividade de fitomassa da mesma planta de cobertura
Cover crops for the northwest region from São Paulo State, Brazil
Keywords: semeadura direta; manejo sustentável do solo; matéria seca; densidade de semeadura; no tillage; sustainable soil management; dry matter; sowing density